A Structural Model for the Role of Knowledge Hiding Behavior and Distrust in the Indirect Effect of Abusive Supervision on Turnover Intention: A Field Study on the Ready-Made Clothes Industry in Port Said - Nour-Eldin, Amr Ahmed; El-Hariry, Basma Mohamed Idris (The Arab Journal of Administration, 2025)
The purpose of this study was to assess the role of hidden knowledge behavior and distrust in the indirect effects (mediator) of abusive supervision on workers’ intention to leave ready-made clothing organizations in the industrial port-said free zone. The simple random sampling method was used to select the items of the research sample. A sample of 377 was distributed among the respondents, the data collected by the questionnaire, while a usable sample of 355 was retained for the analysis, and the response rate was 95.5%. The data was analyzed by structural equation modelling (SEM) using AMOS V.25.The results concluded that support the research hypotheses, which state that there is a direct positive effect of abusive supervision on turnover intention, which is a reflection from the employees towards the abusive supervision exercised on them. It was also found that there is a direct positive effect of knowledge hiding on distrust. In addition, there is a direct positive effect of knowledge hiding and distrust on turnover intention.Moreover, supporting the indirect effect of knowledge hiding on turnover intention through the mediation of distrust, where distrust increased the effect of knowledge hiding on turnover intention, support the indirect effect of abusive supervision on distrust by mediating knowledge hiding, where knowledge hiding increases the effect of abusive supervision on distrust. Finally, supporting the indirect effect of abusive supervision on turnover intention by mediating both knowledge hiding and distrust, we found that withholding knowledge hiding and distrust together increased the effect of abusive supervision on turnover intention.Therefore, top management must be aware that individuals who are subject to abusive supervision will have a greater turnover intention. This intention increases more because they are exposed to knowledge hiding because they will realise that the work environment is not suitable for development and learning, and turnover intention also increases more in distrust. Therefore, trust must be rebuilt and strengthened.